“Viva, viva il Tricolore” Which Citizenship Education in Italian Schools? - Angela Biscaldi (Antropologia, 2017)
The overall aim of this paper is to draw attention to a number of educational practices through which the 2012 Law “Rules for Acquiring Knowledge and Skills relating to «Citizenship and the Constitution» and for teaching the Italian national anthem (the Hymn of Mameli) in schools” is being implemented. In particular, this paper focuses on the description of the 2015/2016 school year-end party dedicated to the theme of citizenship education that involved 100 children aged 3 to 6 in a municipal nursery school in that part of the Po Valley bordering between Lombardy and Emilia Romagna. The goal is to discuss how the notion of national belonging is proposed to new generations and hence how individual and collective imagination is shaped and how cultural identity and memory are reproduced. Also, it focuses on the question of whether the idea of nationhood as channeled through these educational micro-practices is a way of allowing an inclusive notion of nationhood to become established.